MO107CLINICAL CHARACTERISTICS OF A PATIENT POPULATION WITH ATYPICAL HAEMOLYTIC URAEMIC SYNDROME AND MALIGNANT HYPERTENSION: THE GLOBAL AHUS REGISTRY ANALYSIS. (29th May 2021) - Halimi, Jean-Michel; Al-Dakkak, Imad; Anokhina, Katerina; Ardissino, Gianluigi; Licht, Christoph; Lim, Wai; Massart, Annick; Schaefer, Franz; Van de Walle, Johan; Rondeau, Eric
Abstract: Background and Aims: Atypical haemolytic uraemic syndrome (aHUS) is a rare disease that manifests as complement-mediated thrombotic microangiopathy (TMA), which can lead to severe organ damage. Some patients with aHUS may present with malignant hypertension (MHT); both conditions can result in TMA. The objective of this analysis was to characterise patients with aHUS and MHT. Method: In this analysis, patients from the Global aHUS Registry (NCT01522183) were included if they were diagnosed with MHT and were followed ≥90 days after initial aHUS symptom presentation or diagnosis date; patients were excluded if they withdrew from the registry or discontinued treatment with eculizumab due to a diagnosis other than aHUS. Demographics and clinical characteristics were evaluated. Results: Seventy-one of 1903 registry patients were included in the analysis. Clinical characteristics are presented in the table. Seventeen patients (24%) had a paediatric (<18 years) onset of disease, and 54 (76%) were adults at aHUS diagnosis; female patients were slightly overrepresented (61%). Sixty-nine percent of patients were reported to have MHT at around the same time as aHUS diagnosis (+/-2 months), while 11% and 13% experienced MHT before and after aHUS diagnosis, respectively. aHUS triggering conditions were reported in 6/71 patients (8%) (Table ). Cardiovascular (27%) and gastrointestinal (21%) symptoms were the most commonly reported extra-renal manifestations. Eight patients (11%) had a reported family history of aHUS and 40 patients (56%) had a complement pathogenic variant or an anti-CFH-antibody. Thirty-three patients (46%) had a kidney transplant; of these, 20 were prescribed eculizumab in the peri- or post-transplant period. Conclusion: In this analysis of patients with aHUS and MHT, the observed high prevalence of pathogenic variants in complement genes or anti-CFH antibodies, alongside the high proportion of patients with extrarenal manifestations and/or requiring kidney transplant, indicate a high severity of presentation and poor prognosis of aHUS associated with MHT.